Integration of Spiritual Values and Professional Competence in Human Resource Development in Islamic Educational Institutions - Sinta Khoiril Bariyyah; Zumrotul Amalia Abrori; Dewi Cahyani; Moh Ali (FKIP - Universitas Riau, 2026)
Human Resource (HR) development is a key factor in achieving sustainable educational quality. In the context of Islamic educational institutions, HR development is not only directed at improving the professional competence of teachers and education personnel, but also the formation of spiritual character based on Islamic values. This article aims to analyze the concept and model of HR development based on Islamic values that are relevant to be applied in integrated Islamic schools. The method used is library research by examining modern human resource management theory and the principles of developing perfect human beings in Islam. HR development results can be realized through a holistic approach that emphasizes aspects of tazkiyah (purification of the soul), takwiyah (strengthening professional competence), and tarbiyah (formation of character and Islamic work culture). This model is expected to be able to produce educators who are professionally competent, ethical, and oriented towards devotion to Allah SWT.